(untitled) (Ustozlar uchun, 2025)
This article explores the emergence of zoonotic viruses and the pandemic risks associated with human activities. Deforestation, urbanization, wildlife trade, and intensive agriculture increase human-wildlife interactions, facilitating viral spillover events. The study examines the ecological, epidemiological, and socio-economic factors driving zoonotic transmission, with case studies including SARS-CoV, MERS-CoV, Ebola, and SARS-CoV-2. By analyzing historical outbreaks and current preventive measures, the research emphasizes the importance of integrated surveillance, public health preparedness, and environmental management to mitigate pandemic risks. The findings highlight that human-driven ecological disruption is a major contributor to the emergence of novel pathogens and global health threats.¹